Features of Isotypic Structure of Virus-Specific Systemic Humoral Immune Response in Adult Volunteers Immunized with Inactivated Monovalent Subunit Vaccines against Pandemic Influenza A(H1N1)pdm09 - A. A. Vasileva; V. Z. Krivitskaya; E. M. Vojcekhovskaya; V. S. Vakin; E. V. Kuznecova; E. R. Petrova; A. A. Go; N. I. Lvov; A. A. Sominina (Эпидемиология и вакцинопрофилактика)
An isotypic structure of system antibody response to influenza A(H1N1)pdm09 was analyzed in adult volunteers vaccinated with two inactivated monovalent subunit vaccines against pandemic influenza. The comparison group consisted of patients infected with influenza A(H1N1)pdm09 virus. In vaccinated volunteers the more active response of influenza-specific antibodies both with neutralizing properties (IgG1, IgG2, IgG3) and associated with allergic inflammation (IgG and IgE) was observed in comparison with infected patients. The high activity of the virus-specific serum IgA was observed both in infected patients and vaccinated volunteers. Antiviral hemagglutinating activity of antibodies in post-vaccination sera of vaccinated volunteers, unlike sera obtained from infected patients in the phase of recovery, were higher than protective level (1:40) according to HAI data.